Frequency and Amplitude Dependence of Magnetorheological Elastomers Composites. (June 2019) - Moksin, N; Shuib, R K; Ismail, H; Harun, M K
Abstract: In this study, anisotropic and isotropic magnetorheological elastomers (MREs) based on nickel zinc ferrite and natural rubber were prepared. The amount of nickel zinc ferrite was varied at five different levels (20, 40, 60, 80, and 100 phr) to assess its optimum content for enhancing dynamic mechanical performance of MREs. Tan δ was measured through parallel plate rheometer over frequency range of 0.1-100 Hz and strain amplitude range of 0.1-6%. The results revealed that tan δ increased with increasing waste nickel zinc ferrite content and reached maximum value at 100 phr for both isotropic and anisotropic MREs. SEM micrograph showed that anisotropic MREs had chain-like columnar structures of magnetic particles in the matrix as a consequence of an applied magnetic field during curing. For frequency sweep test, tan δ for anisotropic MRE improved 244% and for strain amplitude test 159% improvement compared to isotropic MRE.